Characterization of the binding ability of the odorant binding protein BminOBP9 of Bactrocera minax to citrus volatiles. Issue 3 (21st October 2020) - Yao, Runxian; Zhao, Mingming; Zhong, Ling; Li, Yi; Li, Dazhi; Deng, Ziniu; Ma, Xianfeng
Abstract: BACKGROUND: Bactrocera minax, one of the most important citrus pests, oviposits exclusively on citrus fruit. In the insect olfactory system, odorant‐binding proteins (OBPs) facilitate the initial recognition role of host odor molecules. The aim of this study was to characterize the functional OBPs of B. minax and identify specific volatile organic compounds in the Citrus genus as OBP targets. RESULTS: BminOBP9 ( BminGOBP99a ), a closely related homolog of BdorGOBP99a, which reduces the egg‐laying behavior of Bactrocera dorsalis through silencing technology, was cloned, expressed, and purified. The binding ability of BminOBP9 to 11 citrus volatiles was then examined using fluorescence competition binding assays (FCBA). The results demonstrated that BminOBP9 could bind to all tested citrus volatiles, as could BdorGOBP99a, ZcucGOBP99a, and ZtauGOBP99a. Interestingly, the binding ability of BminOBP9 was the strongest among the four, suggesting that BminOBP9 may have a function in the specific recognition of citrus volatiles. Furthermore, we aligned the above four proteins and found nine distinctive amino acid sites in BminOBP9. To identify the unique binding sites of BminOBP9, we produced the nine mutants using site‐directed mutagenesis. Further FCBA showed that the binding ability of the nine mutants to citrus volatiles significantly reduced, and six of them (substitutes S24P, L36F, E53K, N68D, D112A, and S118R) had the weakest binding ability. CONCLUSION: The results demonstrated that BminOBP9 was the specific protein involved in the perception of citrus host volatiles by B. minax . Moreover, BminOBP9 could prove efficient in screening the candidate odors for pest management. © 2020 Society of Chemical Industry Abstract : BminOBP9 has six distinctive amino acid sites compared with the OBP9 homologs in three other flies, each site shows stronger binding ability to the volatile organic compounds of citrus plant.